Baltica in the Cryogenian, 850–630 Ma - Pease V.; Daly J.S.; Elming S.A.; Kumpulainen R.; Moczydlowska M.; Puchkov V.N.; Roberts D.; Saintot A.; Stephenson R. (My University, 2008)
This new tectonic synthesis provides a framework for understanding the dynamic evolution of Baltica and for constraining tectonic correlations within the context of the Neoproterozoic break-up of Rodinia–Pannotia. Cryogenian Baltica is described with respect to five geographic regions: the northwest, northeast, east, south, and southwest (modern coordinates). These geographic regions define three principal Cryogenian tectonic margins: a rifting northwestern margin, a passive northeastern margin, and a poorly understood southern margin. The northwest region is characterized by Neoproterozoic to lower Ordovician sedimentary successions deposited on Archean to late Mesoproterozoic crystalline complexes, reworked during Caledonian orogenesis. Lare Neoproterozoic to lower Ordovician sedimentary strata record the change from an alluvial setting to a marine environment, and eventually to a partially starved (?) turbidite basin. They document rifting from the Rodinian-Pannotian supercontinent, which was unsuccessful until ca. 620–550 Ma when voluminous dikes and mafic/ultramafic complexes were intruded. Baltica’s northeastern and eastern regions document episodic intracratonic rifting throughout the Mesoproterozoic, followed by pericontinental passive margin deposition throughout the Cryogenian. In the northeast platformal and deeper-water basin deposits are preserved, whereas the eastern region was later affected by Paleozoic rifting and preserves only shelf deposits. The northeastern and eastern regions define Baltica’s Cryogenian northeastern tectonic margin, which was an ocean-facing passive margin of the Rodinia–Pannotia supercontinent. It remained a passive margin until the onset of Timanian orogenesis at ca. 615 Ma, approximately synchronous with the time of Rodinia–Pannotia rifting.
Keywords: Baltica; Rodinia; Neoproterozoic; Orogeny; Paleogeography; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская